2021
DOI: 10.2166/wst.2021.170
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of micropollutant cephalexin by ultraviolet (UV) and assessment of residual antimicrobial activity of transformation products

Abstract: Cephalexin (CEX) is an antibiotic commonly used to treat bacterial infections in humans and animals. However, it can be considered a micropollutant. Thus, this study evaluated the degradation of CEX using ultraviolet irradiation (UV-C) and analyzed the by-products as well as their residual antimicrobial activity. A reactor with a mercury vapor lamp was used for the degradation. Irradiated CEX solution were collected over a period of 4 h and analyzed by High Performance Liquid Chromatography coupled with Mass S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The proposed fragmentation pattern leading to these lactam species is shown in Scheme 2, where the main steps in the pathway are decarboxylation and oxidation reactions. Among major mass peaks throughout the spectrum, we observed several fragments consistent with byproducts already identified for cephalexin subjected to forced degradation [26,33,38] . For example, the peak m/z 214 can be assigned to the so‐called impurity B (mass=214.2, Scheme 2 #3 ) [38] and the peak m/z 304 is compatible with a degradation product formed from the decarboxylation of the native cephalexin (Scheme 2, #2 ).…”
Section: Resultsmentioning
confidence: 52%
See 4 more Smart Citations
“…The proposed fragmentation pattern leading to these lactam species is shown in Scheme 2, where the main steps in the pathway are decarboxylation and oxidation reactions. Among major mass peaks throughout the spectrum, we observed several fragments consistent with byproducts already identified for cephalexin subjected to forced degradation [26,33,38] . For example, the peak m/z 214 can be assigned to the so‐called impurity B (mass=214.2, Scheme 2 #3 ) [38] and the peak m/z 304 is compatible with a degradation product formed from the decarboxylation of the native cephalexin (Scheme 2, #2 ).…”
Section: Resultsmentioning
confidence: 52%
“…Very interesting studies have demonstrated the potential of ultraviolet radiation for remediation of micropollutants derived from cephalexin and other antibiotics. [16,26,42] However, these studies rely on the use of UVC light, which is a virtually nonexistent component in sunlight reaching the earth's surface. [43] In this context, the findings presented here demonstrate that irradiation of sunlight on cephalexin improperly discarded in the environment likely produces byproducts with the capacity to substantially affect the balance of the microbiota.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations